Conversion surgery for advanced pancreatic cancer - Hank, Thomas; Strobel, Oliver (Journal of Clinical Medicine, 2019)
While primarily unresectable locally advanced pancreatic cancer (LAPC) used to be an indication for palliative therapy, a strategy of neoadjuvant therapy (NAT) and conversion surgery is being increasingly used after more effective chemotherapy regimens have become available for pancreatic ductal adenocarcinoma. While high-level evidence from prospective studies is still sparse, several large retrospective studies have recently reported their experience with NAT and conversion surgery for LAPC. This review aims to provide a current overview about different NAT regimens, conversion rates, survival outcomes and determinants of post-resection outcomes, as well as surgical strategies in the context of conversion surgery after NAT. FOLFIRINOX is the predominant regimen used and associated with the highest reported conversion rates. Conversion rates considerably vary between less than 5% and more than half of the study population with heterogeneous long-term outcomes, owing to a lack of intention-to-treat analyses in most studies and a high heterogeneity in resectability criteria, treatment strategies, and reporting among studies. Since radiological criteria of local resectability are no longer applicable after NAT, patients without progressive disease should undergo surgical exploration. Surgery after NAT has to be aimed at local radicality around the peripancreatic vessels and should be performed in expert centers. Future studies in this rapidly evolving field need to be prospective, analyze intention-to-treat populations, report stringent and objective inclusion criteria and criteria for resection. Innovative regimens for NAT in combination with a radical surgical approach hold high promise for patients with LAPC in the future.
Gesehen am 21.01.2020